Meta Analysis the Effects of Asbestos and Silica Dust on the Risk of Lung Cancer among Workers - Aurina Firda Kusuma Wardani; Sumardiyono Sumardiyono; Bhisma Murti (Journal of Epidemiology and Public Health, 2022)
Background: Lung cancer is a cancer whose incidence increases every year and is the number one cancer cause of death in the world. One of the causes of lung cancer comes from occupational exposure in the form of asbestos dust and silica. This study aims to analyze the effect of exposure to asbestos and silica dust on the incidence of lung cancer in the working community.Subjects and Method: This study is a meta-analysis with the following PICO, population: working society. Intervention: exposure to asbestos dust and silica dust. Comparison: not exposed to asbestos dust and silica dust. Result: lung cancer. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. The keywords to search for articles were “dust exposure” OR “silica dust exposure” OR “asbestos dust exposure” OR “occupational dust exposure” AND “lung cancer”. The articles included are full-text English with a case-control study design from 2007 to 2022. The articles were selected using PRISMA flow diagrams. Articles were analyzed using the Review Manager 5.3 application.Results: A total of 14 case-control studies from continental Europe, America and Asia were selected for systematic review and meta-analysis. Based on 8 studies on the effect of exposure to asbestos dust on the incidence of lung cancer, the incidence of lung cancer increased 1.57 times compared to workers who were not exposed to asbestos dust (aOR= 1.57; 95% CI= 1.20 to 2.06; p= 0.001) and 9 case-control studies on the effect of exposure to silica dust showed an increase of 1.31 times the incidence of lung cancer compared to workers who were not exposed to silica dust (aOR = 1.31; 95% CI = 1.25 to 1.38; p<0.001).Conclusion: Exposure to asbestos and silica dust increases the incidence of lung cancer in workers. Keywords: asbestos, silica, occupational dust exposure, lung cancer. Correspondence:Aurina Firda Kusuma Wardani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Mobile: +6282135012135. Email: firdakw@gmail.com.